First Mildly Ill, Nonhospitalized Case of Coronavirus Disease 2019 (COVID-19) Without Viral Transmission in the United States—Maricopa County, Arizona, 2020. (2nd April 2020) - Scott, Sarah E; Zabel, Karen; Collins, Jennifer; Hobbs, Katherine C; Kretschmer, Melissa J; Lach, Mitchell; Turnbow, Katie; Speck, Lindsay; White, Jessica R; Maldonado, Keila; Howard, Brandon; Fowler, Jeanene; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) causes a range of illness severity. Mild illness has been reported, but whether illness severity correlates with infectivity is unknown. We describe the public health investigation of a mildly ill, nonhospitalized COVID-19 case who traveled to China. Methods: The case was a Maricopa County resident with multiple severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–positive specimens collected on 22 January 2020. Contacts were persons exposed to the case on or after the day before case diagnostic specimen collection. Contacts were monitored for 14 days after last known exposure. High-risk contacts had close, prolonged case contact (≥ 10 minutes within 2 m). Medium-risk contacts wore all US Centers for Disease Control and Prevention–recommended personal protective equipment during interactions. Nasopharyngeal and oropharyngeal (NP/OP) specimens were collected from the case and high-risk contacts and tested for SARS-CoV-2. Results: Paired case NP/OP specimens were collected for SARS-CoV-2 testing at 11 time points. In 8 pairs (73%), ≥ 1 specimen tested positive or indeterminate, and in 3 pairs (27%) both tested negative. Specimens collected 18 days after diagnosis tested positive. Sixteen contacts were identified; 11 (69%) had high-risk exposure, including 1 intimate contact, and 5 (31%) had medium-risk exposure. In total, 35 high-risk contact NP/OP specimens were collected for SARS-CoV-2 testing; all 35 pairs (100%) tested negative. Conclusions: This report demonstrates that SARS-CoV-2 infection can cause mild illness and result in positive tests for up to 18 days after diagnosis, without evidence of transmission to close contacts. These data might inform public health strategies to manage individuals with asymptomatic infection or mild illness. Abstract : We describe the public health investigation of the first mildly ill, nonhospitalized US COVID-19 case. Despite specimens testing positive 18 days after diagnosis, no severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission occurred among 10 high-risk contacts, including 1 intimate contact, based on serial SARS-CoV-2 testing.